2006
DOI: 10.1287/mksc.1050.0144
|View full text |Cite
|
Sign up to set email alerts
|

Research on Innovation: A Review and Agenda forMarketing Science

Abstract: I nnovation is one of the most important issues in business research today. It has been studied in many independent research traditions. Our understanding and study of innovation can benefit from an integrative review of these research traditions. In so doing, we identify 16 topics relevant to marketing science, which we classify under five research fields: • Consumer response to innovation, including attempts to measure consumer innovativeness, models of new product growth, and recent ideas on network externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
631
0
28

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 909 publications
(698 citation statements)
references
References 289 publications
(216 reference statements)
11
631
0
28
Order By: Relevance
“…He pointed out that only firms that sell products with a longer product cycle are willing to undertake product innovation in times of market uncertainty. However, Zhou, Yim, and Tse (2005) found that demand uncertainty has a positive effect on innovation, whereas Hauser, Tellis, and Griffin (2006) believed that in a market with high turbulence, where customers demand new products or upgrades, pressure is naturally put on product innovation rather than on process innovation. They posited that turbulence has a positive effect on innovation.…”
Section: Moderating Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…He pointed out that only firms that sell products with a longer product cycle are willing to undertake product innovation in times of market uncertainty. However, Zhou, Yim, and Tse (2005) found that demand uncertainty has a positive effect on innovation, whereas Hauser, Tellis, and Griffin (2006) believed that in a market with high turbulence, where customers demand new products or upgrades, pressure is naturally put on product innovation rather than on process innovation. They posited that turbulence has a positive effect on innovation.…”
Section: Moderating Effectsmentioning
confidence: 99%
“…Moreover, although previous research has studied the effects of alliances on product innovation, little is known about how alliances affect product and process innovations (Hauser, Tellis, & Griffin, 2006). In the present study, we investigate the different effects of the explorative and exploitative alliances on the product and process innovations, thus offering an additional perspective on managing different types of innovation.…”
Section: Introductionmentioning
confidence: 98%
“…About innovation strategies of retail industry, the research of Hauser, Tellis, and Griffin (2006) shows that measures of innovation performance, including new products, new processes and modifications can result in best practices, developing a competitive strategy. In the view of Woodside, Ko, and Huan (2012), the current competitive landscape which retail companies are entered requires an extreme emphasis on price, quality and customer satisfaction, demanding a greater recognition of innovation as a strategic competence.…”
Section: Retail Strategiesmentioning
confidence: 99%
“…Of course, there are many recent uses of sensitivity analysis for this purpose (e.g., Sriram et al 2006, Ho et al 2006, Lewis et al 2006, Naik 2005, Chintagunta 2005, Mitra and Golder 2006. Mazzeo (2006) (Hauser et al 2006). However, they cite research using output measures for evaluation.…”
Section: Descriptive (Positive) Models Vs Prescriptive (Normative) Mmentioning
confidence: 99%